High Throughput Sequencing (HTS) – based identification and characterization of Geminiviridae family members in weeds associated with the tomato crop in Brazil - Lima, Eduardo Soares da Silva (2023)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Fitopatologia, 2023.